Revisiting supersaturation as a factor determining amyloid fibrillation. (February 2016) - So, Masatomo; Hall, Damien; Goto, Yuji
Graphical abstract: Highlights: Amyloid fibrils are formed by a nucleation-growth mechanism. Formation of amyloid fibrils is similar to the crystallization of solutes. Solubility and supersaturation are important factors of amyloid fibrillation. Amyloid fibrillation competes with amorphous aggregation. Formation of distinct aggregates was explained by a competition mechanism. Abstract : Amyloid fibrils involved in various diseases are formed by a nucleation-growth mechanism, similar to the crystallization of solutes from solution. Solubility and supersaturation are two of the most important factors determining crystallization of solutes. Moreover, crystallization competes with glass formation in which solutes collapse into amorphous aggregates. Recent studies on the formation of amyloid fibrils and amorphous aggregates indicate that the partition between distinct types of aggregates can be rationally explained by a kinetic and thermodynamic competition between them. Understanding the role of supersaturation in determining aggregation-based phase transitions of denatured proteins provides an important complementary point of view to structural studies of protein aggregates.